2021
DOI: 10.1123/ijspp.2019-0727
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Markers of Muscle Damage Throughout the Menstrual Cycle

Abstract: Context: The indirect markers of muscle damage have been previously studied in females. However, inconclusive results have been found, possibly explained by the heterogeneity regarding monitoring and verification of menstrual-cycle phase. Purpose: To determine whether the fluctuations in sex hormones during the menstrual cycle influence muscle damage. Methods: A total of 19 well-trained eumenorrheic women (age 28.6 [5.9] y; height 163.4 [6.1] cm; weight 59.6 [5.8] kg body mass) performed an eccentric-based res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…Perceived soreness and exertion appeared to be unaffected by MC phase. This is in contrast with the findings of previous studies that have found, under standardised conditions, muscle soreness before [ 42 ] and immediately post exercise [ 43 ] is greatest in the early follicular phase. However, delayed onset muscle soreness (24 and 48 h post-exercise) was not significantly affected by MC phase [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Perceived soreness and exertion appeared to be unaffected by MC phase. This is in contrast with the findings of previous studies that have found, under standardised conditions, muscle soreness before [ 42 ] and immediately post exercise [ 43 ] is greatest in the early follicular phase. However, delayed onset muscle soreness (24 and 48 h post-exercise) was not significantly affected by MC phase [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the current protocol successfully induced muscle damage, but no significant differences were observed between the two groups in each measure. As a previous study reported no phase differences in indirect markers of muscle damage after eccentric exercise [ 37 ], differences in ovarian hormone concentrations in MCs are not expected to affect the indirect markers of muscle damage.…”
Section: Discussionmentioning
confidence: 85%
“…This study recruited individuals with between-group differences by prioritizing the exclusion of the repeated bout effect, which should be considered in data comparisons. Originally, this study was supposed to use a random crossover design; however, previous studies that used a crossover design were influenced by the repeated bout effect, which is characteristic of eccentric exercise due to the short period between each bout of exercises [ 32 , 37 ]. Thus, although the results of the present study may be more influenced by individual differences in ovarian hormone concentrations than by the random crossover design, we evaluated a complete methodology for MC phase verification.…”
Section: Discussionmentioning
confidence: 99%
“…These eumenorrheic participants were analyzed earlier to observe the muscle damage response between menstrual cycle phases. 26,27 Further exclusion criteria included (1) the use of any hormonal contraception or HRT in the 6 months preceding the study, (2) any pregnancies in the year preceding the study, (3) any existing disease and/or metabolic or hormonal disorder, (4) any musculoskeletal injury in the past 6 months, (5) any surgery interventions (ie, ovariectomy) or other medical conditions that would be exacerbated by an eccentric resistance exercise protocol, (6) the regular use of medication or dietary supplements that could affect the results, and (7) smoking. A written informed consent was obtained from each participant.…”
Section: Participantsmentioning
confidence: 99%
“…Verification of menstrual cycle phases in eumenorrheic participants was performed according to the studies carried out previously by our research group, 26,27 following the methodological recommendations based on a 3-step method 16 including (1) calendar counting, (2) home urine tests to detect luteinizing hormone (LH) surge and the subsequent ovulation between 14 and 26 hours later, 16 and (3) blood hormones' analysis.…”
Section: Determination Of Menstrual Cycle Phasesmentioning
confidence: 99%